2020
DOI: 10.1016/j.numecd.2020.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Overall dietary variety and adherence to the Mediterranean diet show additive protective effects against coronary heart disease

Abstract: Background and aim: Along with the increasing evidence of the cardioprotective effects of the Mediterranean Diet (MD), the scientific interest and advocacy of dietary variety as a potentially healthy eating habit gradually faded, until its complete oblivion in the latest European cardiovascular prevention guidelines. Our study aims to investigate whether dietary variety adds to the "Mediterranean-ness" of the diet in protecting against coronary heart disease (CHD). Methods and results: In this caseecontrol Ita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…The PREDIMED study also found similar results for the Mediterranean diet arms of the intervention, where a reduction of carbohydrates and the increase of monounsaturated dietary fatty acids (MUFA) resulted in lower cholesterol levels and increased HDL cholesterol levels [46]. Similar results were reported from another recent randomized control trial from Italy [47]. In summary, the present study is consistent with past research demonstrating that the Mediterranean diet has cardioprotective effects by improving HDL-cholesterol levels and the total cholesterol/HDL ratio [19,23,48].…”
Section: Discussionsupporting
confidence: 70%
“…The PREDIMED study also found similar results for the Mediterranean diet arms of the intervention, where a reduction of carbohydrates and the increase of monounsaturated dietary fatty acids (MUFA) resulted in lower cholesterol levels and increased HDL cholesterol levels [46]. Similar results were reported from another recent randomized control trial from Italy [47]. In summary, the present study is consistent with past research demonstrating that the Mediterranean diet has cardioprotective effects by improving HDL-cholesterol levels and the total cholesterol/HDL ratio [19,23,48].…”
Section: Discussionsupporting
confidence: 70%
“…Regarding the MED participant countries, analogous results with scores in the midrange of the scale were previously reported in SP [ 15 , 16 , 28 , 30 , 37 , 42 , 43 ], PT [ 22 , 44 , 45 ], IT [ 17 , 18 , 46 , 47 , 48 , 49 ], GR [ 50 , 51 ], and CY [ 52 ]. Other Southern European as well as some non-European MED countries [ 23 , 27 , 53 ] have also been attributed a moderate value of MD adherence.…”
Section: Discussionsupporting
confidence: 82%
“…Rice is an important staple food for more than half of the world's population [72], representing one of the main sources of carbohydrate with an important role in a healthy diet [68]. However, it should be considered as part of a balanced and varied diet [12,13]. Indeed, cereals, including rice, should be present at each meal together with healthy proteins, plant-based fat, vegetables, and fruits [34].…”
Section: Discussionmentioning
confidence: 99%
“…Mediterranean diet (MD) has been widely described to positively impact health status [11]. According to the MD dietary guidelines, it is necessary to consume different food categories every day to guarantee nutrient balance in the diet [12,13]. Cereals are one of the pillars of the Mediterranean diet and they should be part of every daily meal [14,15].…”
Section: Introductionmentioning
confidence: 99%